Structural, Dielectric and Electrical Properties of Zirconium Doped Barium Titanate Perovskite (Journal of Bangladesh Academy of Sciences, 2009)
The microstructural and electrical properties of pure and Zirconium (Zr) doped Barium titanate (BT) samples with general formula Ba(Ti1-xZrx)O3 (where x=0.0, 0.1, 0.2 and 0.3), prepared by high temperature solid state reaction at a sintering temperature of 1250Â° C, were investigated. Dielectric and structural properties of BT ceramics is influenced significantly by small addition of ZrO2. Scanning Electron Microscope (SEM) observations revealed enhanced microstructural uniformity and retarded grain growth with increasing Zr content. The dielectric study with frequency at room temperature in the frequency range 75 kHz to 30 MHz shows that dielectric constant decreases with increasing frequency. The resistivity of the samples shows asymptotic behavior with the variation of frequency and was found to be of the order of ~103 Î©-m. Loss factor of the grown materials decreased with increasing frequency but it became independent at higher frequency range. doi: 10.3329/jbas.v32i2.2434 Journal of Bangladesh Academy of Sciences Vol.32(2) 2008 151-159